RECONSTRUCTION OF MORAL AND SPIRITUAL CONCEPTS IN THE TRANSLATION OF UZBEK LITERATURE (based on abdulla qodiriy’s novel past days) (International journal of artificial intelligence, 2026)
This article explores the challenges and strategies involved in reconstructing moral and spiritual concepts in the translation of Uzbek literature, with a focus on Abdulla Qodiriy’s novel Past Days. The study emphasizes the significance of conveying culturally embedded values, ethical norms, and spiritual dimensions in translated texts. By analyzing selected passages, the paper demonstrates how translators navigate linguistic, cultural, and contextual differences to preserve the author’s intended moral and spiritual meaning. The findings highlight that effective translation requires not only linguistic competence but also deep cultural understanding and sensitivity to the ethical and spiritual nuances of the source text.